An Early Jurassic age for the Puchezh‐Katunki impact structure (Russia) based on 40Ar/39Ar data and palynology. (29th May 2019) - Holm‐Alwmark, S.; Alwmark, C.; Ferrière, L.; Lindström, S.; Meier, M. M. M.; Scherstén, A.; Herrmann, M.; Masaitis, V. L.; Mashchak, M. S.; Naumov, M. V.; Jourdan, F.
Abstract: The Puchezh‐Katunki impact structure, 40–80 km in diameter, located 400 km northeast of Moscow (Russia), has a poorly constrained age between 164 and 203 Ma (most commonly quoted as 167 ± 3 Ma). Due to its relatively large size, the Puchezh‐Katunki structure has been a prime candidate for discussions on the link between hypervelocity impacts and extinction events. Here, we present new 40 Ar/ 39 Ar data from step‐heating analysis of five impact melt rock samples that allow us to significantly improve the age range for the formation of the Puchezh‐Katunki impact structure to 192–196 Ma. Our results also show that there is not necessarily a simple relationship between the observed petrographic features of an impact melt rock sample and the obtained 40 Ar/ 39 Ar age spectra and inverse isochrons. Furthermore, a new palynological investigation of the postimpact crater lake sediments supports an age significantly older than quoted in the literature, i.e., in the interval late Sinemurian to early Pliensbachian, in accordance with the new radioisotopic age estimate presented here. The new age range of the structure is currently the most reliable age estimate of the Puchezh‐Katunki impact event.